Relación entre las percepciones de los estilos de crianza de padres y sus hijos que cursan cuarto grado de primaria en un colegio privado de la ciudad de Bogotá (2019)
The main objective of the research presented was to establish the relationship between the perceptions of parenting styles and their children who attend the fourth grade of primary school in a private school in the city of Bogotá. This is a study with a quantitative approach, of a descriptive type, with a non-experimental design, in which the Scale of PEF was used as an instrument for collecting information: Scale for the Identification of Family Educational Practices in their abbreviated versions that were answered by 20 parents and their children belonging to single-parent families. The results show that in this research sample the parenting styles exercised by parents coincide with those perceived by their children, whether authoritarian, democratic or permissive.